2020
DOI: 10.1242/bio.050096
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin18 regulates angiogenesis through VEGFR2 and Notch pathways

Abstract: The VEGF pathway is critically required for vasculogenesis, the formation of the primary vascular network. It is also required for angiogenesis resulting in sprouting and pruning of vessels to generate mature arborizing structures. The Notch pathway is essential for arterial–venous specification and the maturation of nascent vessels. We have determined that Tspan18, a member of the Tetraspanin family, is expressed in developing vessels but not in mature vasculature in zebrafish and mouse wound healing. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Other proteins, such as BMP4, BMPER, Dll1, Edn1, and Tspan18, have all been shown to promote angiogenesis and vascular patterning. 47 , 48 More investigations are required to identify what are the critical downstream signals that mediate the function of Heg in regulating liver vascular patterning.…”
Section: Discussionmentioning
confidence: 99%
“…Other proteins, such as BMP4, BMPER, Dll1, Edn1, and Tspan18, have all been shown to promote angiogenesis and vascular patterning. 47 , 48 More investigations are required to identify what are the critical downstream signals that mediate the function of Heg in regulating liver vascular patterning.…”
Section: Discussionmentioning
confidence: 99%
“…More mechanistic insights into the VEGF–Notch–Eph/ephrin axis for arterial specification have been gained in recent years. It has been shown that tetraspanin 18 regulates both Notch and VEGF signalling during developmental angiogenesis [ 30 ]. Benedito and co-workers [ 31 ] demonstrated that elevated VEGF and Notch levels suppress the cell cycle and promote enrolment of ECs into arteries.…”
Section: Notch and Vascular Developmentmentioning
confidence: 99%
“…Tetraspanins are widely expressed in teleosts [ 9 ] but there are no reports of roles in fish fertility. Several tetraspanins have roles during zebrafish development, including pigment cell interactions [ 10 ], hatching [ 11 ], vascularisation [ 12 , 13 ] migrasome formation [ 14 ] and primordium migration [ 15 ]. However, the role of Cd9 in fertilisation has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%